2003
DOI: 10.1074/jbc.m206421200
|View full text |Cite
|
Sign up to set email alerts
|

RANK Ligand-induced Elevation of Cytosolic Ca2+ Accelerates Nuclear Translocation of Nuclear Factor κB in Osteoclasts

Abstract: RANK ligand (RANKL) induces activation of NFB] i elevation using the intracellular Ca 2؉ chelator 1,2-bis(O-aminophenoxy)ethane-N,N,N,N-tetraacetic acid (BAPTA) abolished the ability of RANKL to enhance osteoclast survival. Using immunofluorescence, NFB was found predominantly in the cytosol of untreated osteoclasts. RANKL induced transient translocation of NFB to the nuclei, which was maximal at 15 min. U73122 or BAPTA delayed nuclear translocation of NFB. Delays were also observed upon inhibition of calcineu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
65
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 46 publications
7
65
1
Order By: Relevance
“…RANKL is known to activate the NF-B transcription complex in preosteoclasts, as well as in mature osteoclasts (29). One study showed that RANKL acts through phospholipase C to release Ca 2ϩ from intracellular stores, thereby accelerating nuclear translocation of NF-B (30). This study also suggested that mediators involved in calcium signaling pathways play an intermediary role connecting signals from RANK of extracellular space to transcription factors, such as NF-B of the nucleus.…”
Section: Discussionmentioning
confidence: 74%
“…RANKL is known to activate the NF-B transcription complex in preosteoclasts, as well as in mature osteoclasts (29). One study showed that RANKL acts through phospholipase C to release Ca 2ϩ from intracellular stores, thereby accelerating nuclear translocation of NF-B (30). This study also suggested that mediators involved in calcium signaling pathways play an intermediary role connecting signals from RANK of extracellular space to transcription factors, such as NF-B of the nucleus.…”
Section: Discussionmentioning
confidence: 74%
“…Various effects of RANKL, including bone resorption by osteoclasts and inhibition of cell death, are mediated through PI 3-kinase, PKC, and phospholipase C pathways (33)(34)(35). Previous studies have shown that Src kinases and phospholipase C are implicated in RANKL-induced endothelial cell migration, whereas 2314 MOSHEIMER ET AL osteoclast chemotaxis toward RANKL is ERK-1/2 dependent (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Like P2Y6, other G protein-coupled receptors that activate NF-B (such as receptors for thrombin, platelet-activating factor, endothelin, and bradykinin) couple through G q to activation of PLC␤ (37). Cytosolic Ca 2ϩ , released through the PLC cascade, can regulate the activity of a variety of transcription factors including NF-B (24,38). Activation of P2Y1, P2Y2, and P2Y6 receptors in osteoclasts induces transient rise in [Ca 2ϩ ] i ; however, only the P2Y6 receptor couples to NF-B activation, indicating that a rise in [Ca 2ϩ ] i alone is not sufficient to activate NF-B in osteoclasts.…”
Section: Discussionmentioning
confidence: 99%